Pelatihan Berpikir Positif untuk Meningkatkan Penerimaan Diri Survivor Bipolar di Yogyakarta - Andhita Dyorita Khoiryasdien; Annisa Warastri (Universitas Muhammadiyah Jember, 2020)
This research is about mood disorders (Bipolar) in the city of Yogyakarta. Yogyakarta has a place for bipolar survivors namely BCI (Bipolar Care Indonesia knot Jogja). Some therapeutic efforts that have been made show that the effectiveness of therapy depends on self-acceptance of ODB (people with bipolar disorder). If ODB still cannot accept that he is diagnosed with bipolar disorder, it will be difficult to be able to accept various types of therapy both psychotherapy and pharmacism. The subjects involved in this study were 10 people. People with ODB are given positive thinking training that is expected to provide a more positive change towards self-acceptance. This research uses a quasi-experimental method. The design used is one group pretest-posttest design. Positive thinking training was conducted six times. Based on the results of the study obtained an increase in positive thinking scores from pretest to posttest. In other words, Positive Thinking Training is effective for increasing self-acceptance of ODB.